Design of a low-cost electrical resistivity meter for near surface surveys - de la Vega, Matias (2021)
A programmable automated electrical resistivity meter was designed and constructed. The device was created to perform near surface studies, particularly for archaeogeophysical target characterization. Real field and laboratory model studies can be performed changing the current input of the device. The equipment consists of two independent devices, each one with its own microcontroller platform. They are interconnected through serial data transfer protocol. The first device, works as a resistivity meter where the ABMN electrode positions are programmed and permits the interaction with the user. The second one, connects the current and voltage channels to the programmed electrode positions. A physical model and field measurements were performed with different electrode configurations such as Dipole-Dipole, Werner-Schlumberger and Wenner γ112 in order to verify the performance of the automated electrical resistivity meter. The measurements give mean relative standard deviation values between 0.6% and 5.5% and data inversion convergence between 1.3% and 7.2%. Even though this open source and low cost electrical resistivity meter was design primarily for archaeogeophysical studies, it could be adapted to other geophysical issues such as contamination plumes detection and characterization, tunnel detection, etc.